2009
DOI: 10.1161/hypertensionaha.109.133223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modest Salt Reduction on Blood Pressure, Urinary Albumin, and Pulse Wave Velocity in White, Black, and Asian Mild Hypertensives

Abstract: Abstract-A reduction in salt intake lowers blood pressure. However, most previous trials were in whites with few in blacks and Asians. Salt reduction may also reduce other cardiovascular risk factors (eg, urinary albumin excretion, arterial stiffness). However, few well-controlled trials have studied these effects. We carried out a randomized double-blind crossover trial of salt restriction with slow sodium or placebo, each for 6 weeks, in 71 whites, 69 blacks, and 29 Asians with untreated mildly raised blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(177 citation statements)
references
References 31 publications
4
167
1
5
Order By: Relevance
“…T, telmisartan 40 mg/day; T+HCT, telmisartan 40 mg/day+hydrochlorothiazide 12.5 mg/day; P, placebo; S, sodium chloride supplementation, NaCl 100 mmol/24 h. Figure adapted with permission from Ekinci et al [10] in individuals with elevated blood pressure, moderate reduction in dietary salt intake over four or more weeks is an effective way of reducing blood pressure [25]. The mean decrease in systolic BP was 5.1 mmHg, with a reduction in urinary sodium of 78 mmol/24 h. Similarly, a recent study showed that moderate sodium restriction corresponding to a 55 mmol/24 h decrease in urinary sodium excretion reduced clinic blood pressure by 4.8 mmHg and daytime ABP by 4.7 mmHg in three ethnic groups [26]. The current study in patients with type 2 diabetes and hypertension supports these findings, since an increase in urinary sodium of 56 mmol/24 h during NaCl supplementation was associated with a 5.6 mmHg blunting of the systolic BP response to telmisartan with or without HCT.…”
Section: Discussionmentioning
confidence: 91%
“…T, telmisartan 40 mg/day; T+HCT, telmisartan 40 mg/day+hydrochlorothiazide 12.5 mg/day; P, placebo; S, sodium chloride supplementation, NaCl 100 mmol/24 h. Figure adapted with permission from Ekinci et al [10] in individuals with elevated blood pressure, moderate reduction in dietary salt intake over four or more weeks is an effective way of reducing blood pressure [25]. The mean decrease in systolic BP was 5.1 mmHg, with a reduction in urinary sodium of 78 mmol/24 h. Similarly, a recent study showed that moderate sodium restriction corresponding to a 55 mmol/24 h decrease in urinary sodium excretion reduced clinic blood pressure by 4.8 mmHg and daytime ABP by 4.7 mmHg in three ethnic groups [26]. The current study in patients with type 2 diabetes and hypertension supports these findings, since an increase in urinary sodium of 56 mmol/24 h during NaCl supplementation was associated with a 5.6 mmHg blunting of the systolic BP response to telmisartan with or without HCT.…”
Section: Discussionmentioning
confidence: 91%
“…Blockade of the reninangiotensin-aldosterone system (RAAS) is well known to reduce urinary albumin excretion, and it is considered a mainstay of therapy in the prevention of ESRD (4,5). The antiproteinuric effect of the RAAS blockade can be magnified or reduced depending on the amount of dietary salt intake (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These data are in sharp contrast with the current literature, which shows a beneficial effect of salt restriction on arterial stiffness. 43,44 The authors provide no explanation for this puzzling finding. The examined population was very small, with approximately one dozen patients enrolled in each of the three studies.…”
Section: Study Limitations and Perspectivesmentioning
confidence: 92%